A vital technology: Review of the literature on mobile phone use among pastoralists - Martin C. Parlasca (Journal of International Development, 2021)
Mobile phones fit well into the lives of pastoralists in low-income countries. The technology is firmly integrated into most pastoralist communities, affecting and transforming several core activities. Most studies concerned with this relationship, however, have narrow regional and thematic foci. The complementarity or discrepancy between relevant research is unknown, and a critical assessment of the current state of research is lacking. This study identifies, summarizes, and analyzes relevant studies, showing that the literature attests generally positive influences of mobile phones although some negative effects also occur. Effects on pastoralists' income, environmental externalities, and gender roles are not yet sufficiently understood.
Keywords: 300; communication; ICT; livestock; mobile phones; pastoralism; rural development